2012
DOI: 10.1051/0004-6361/201219481
|View full text |Cite
|
Sign up to set email alerts
|

HS 1700+6416: the first high-redshift unlensed narrow absorption line-QSO showing variable high-velocity outflows

Abstract: We present a detailed analysis of the X-ray emission of HS 1700+6416, a high-redshift (z = 2.7348) luminous quasar classified as a narrow absorption line (NAL) quasar on the basis of its SDSS spectrum. The source has been observed nine times by Chandra and once by XMM-Newton from 2000 to 2007. Long-term variability is clearly detected between the observations in the 2−10 keV flux, where it varies by a factor of three (∼3−9 × 10 −14 erg s . Most interestingly, one broad absorption feature is clearly detected at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 59 publications
9
59
1
Order By: Relevance
“…-The residuals above the expected energies of Fe Kα suggest the presence of an outflowing disk wind, as predicted by super-Eddington accretion models (e.g., Zubovas & King 2012), and observed in a handful of high-redshift QSOs accreting close to Eddington (Chartas et al 2003;Lanzuisi et al 2012;Vignali et al 2015). The presence of ionized material surrounding the SMBH is indeed one of the characteristics of highly accreting BHs (see, e.g., Ballantyne et al 2011).…”
Section: +198mentioning
confidence: 58%
“…-The residuals above the expected energies of Fe Kα suggest the presence of an outflowing disk wind, as predicted by super-Eddington accretion models (e.g., Zubovas & King 2012), and observed in a handful of high-redshift QSOs accreting close to Eddington (Chartas et al 2003;Lanzuisi et al 2012;Vignali et al 2015). The presence of ionized material surrounding the SMBH is indeed one of the characteristics of highly accreting BHs (see, e.g., Ballantyne et al 2011).…”
Section: +198mentioning
confidence: 58%
“…This average value is close to the velocity derived for the outflow observed in PID352. Compared with other AGN showing UFOs, the peculiarity of PID352 is that it represents one of the few cases where an X-ray outflowing wind has been clearly detected at z > 1 (see also Chartas et al 2002Chartas et al , 2007Chartas et al , 2009Chartas et al , 2014Lanzuisi et al 2012). Furthermore, to our knowledge, PID352 is not a lensed quasar, while most of the z > 1 outflow detections are related to lensed systems.…”
Section: Radio Datamentioning
confidence: 74%
“…At the end of this obscured phase, massive quasar-driven outflows blow away most of the cold gas reservoir, creating a population of "red-and-dead" gas-poor elliptical galaxies (e.g., Cattaneo et al 2009). Support for this picture -at least for the most luminous AGN -comes from observations of kpc-scale outflows of molecular gas (e.g., Feruglio et al 2010;Sturm et al 2011;Veilleux et al 2013;Cicone et al 2014), as well as of neutral and ionized gas (e.g., Nesvadba et al 2008;Alexander et aloutflows (UFOs, with velocities typically up to 0.1-0.4c) have been clearly detected in X-rays in a sizable sample of AGN at low redshift (e.g., Reeves et al 2003;Pounds et al 2003;Tombesi et al 2010Tombesi et al , 2012aTombesi et al , 2014Tombesi et al , 2015Giustini et al 2011;Patrick et al 2012;Gofford et al 2013Gofford et al , 2015King et al 2014;Nardini et al 2015;Ballo et al 2015; see also Cappi 2006 for an early review; and Fabian 2012 for a more recent one) and also in a limited number of high-redshift quasars (e.g., Chartas et al 2002Chartas et al , 2007Chartas et al , 2009Chartas et al , 2014Saez et al 2009;Lanzuisi et al 2012). Although original claims of blueshifted absorption features were strongly debated (see Vaughan & Uttley 2008), recent high photon statistics in X-ray spectra of both radio-quiet (e.g., Tombesi et al 2010Tombesi et al , 2011Tombesi et al , 2012aGofford et al 2013) and radio-loud AGN (e.g., Gofford et al 2013;Tombesi et al 2014) have undoubtedly shown that these outflows are not ra...…”
Section: Introductionmentioning
confidence: 99%
“…The observed wavelengths of the C iv doublet (λλ 1548.20Å, 1550.77Å) imply that the UV absorber is outflowing with a speed of v CIV ∼ 19,400 km s −1 . The only other quasar detected to date with similar blueshifted X-ray absorption features and a narrow absorption line (NAL) outflow is the unlensed z=2.74 NAL quasar HS 1700+6414 (Lanzuisi et al 2012) which, however, has a ∼10 times lower 2-10 keV flux of 3-9×10 −14 erg s −1 cm −2 . Blueshifted X-ray broad absorption lines have been detected in several high-z quasars (i.e., APM 08279+5255, Chartas et al 2002;PG 1115+080, Chartas et al 2003andHS 1700+6416, Lanzuisi et al 2012).…”
mentioning
confidence: 99%